Strategi Pengembangan UMKM Batikayudewi Melalui Sosial Media Instagram - Anjelina Br Hotang; Annisa Ramadani; Fadillah Aulia Rahmah; Sherly Yosevany; Aditya Sugih Setiawan; Samuel Samuel (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2026)
This community service activity aims to improve the effectiveness of Batikayudewi MSME digital promotion by maximizing the use of Instagram as the main marketing platform. Initial observations show that although MSMEs have been regularly uploading content every day, the promotion of workshop packages as the main product has not been running well. Through a series of activities including observation, interviews, guidance in content creation, and improvements to the publication strategy, the PKM team helped improve the quality and consistency of promotional materials. The results of these activities showed an increase in the number of followers, viewers, and positive interactions on both Instagram accounts, both the main account and the supporting account created during the program. In addition to improvements on social media, business owners also gained a deeper understanding of the basic principles of digital marketing, the importance of informative visual content, and consistency in building brand identity. Overall, this community service activity successfully improved the promotional capabilities of MSMEs and strengthened Batikayudewi's readiness to utilize digital media as a sustainable marketing tool.